Moralization and Becoming a Vegetarian: The Transformation of Preferences Into Values and the Recruitment of Disgust - Rozin, Paul; Markwith, Maureen; Stoess, Caryn (Psychological Science, 1997)
We describe a rather common process that we call moralization, in which objects or activities that were previously morally neutral acquire a moral component. Moralization converts preferences into values, and in doing so influences cross-generational transmission (because values are passed more effectively in families than are preferences), increases the likelihood of internalization, invokes greater emotional response, and mobilizes the support of governmental and other cultural institutions. In recent decades, we claim, cigarette smoking in America has become moralized. We support our claims about some of the consequences of moralization with an analysis of differences between health and moral vegetarians. Compared with health vegetarians, moral vegetarians find meat more disgusting, offer more reasons in support of their meat avoidance, and avoid a wider range of animal foods. However, contrary to our prediction, liking for meat is about the same in moral and health vegetarians.